Identifikasi Kesulitan Belajar pada Anak Berkebutuhan Khusus - Habsy, Bakhrudin All; Hafizah, Maryam; Salsabila, Hussana; Melati, Shella (TSAQOFAH, 2024)
In this world, there are individuals who are born and grow up to be normal children as in general and there are also individuals who are born with deficiencies in the form of abnormalities, both physically, mentally, and intellectually. As an Indonesian citizen, every individual has the right to a proper education, including those with disabilities. However, although the law has explicitly regulated equal rights and obligations for every citizen to access education, cases of discrimination in the field of education still often occur, especially against children with special needs. This is because there are still people who have negative assumptions about children with disabilities. However, children with disabilities are children with developmental disabilities, so they inevitably have more difficulty learning than other normal children. Therefore, this article aims to identify the learning difficulties experienced by children with disabilities, especially those with autism, Down syndrome and ADHD and how to handle them. This research uses qualitative methods with data collection techniques in the form of journal literature studies which are analyzed descriptively. Learning difficulties experienced by children due to developmental disorders, especially in children with autism, ADHD, and down syndrome basically have something in common. Namely, they are all usually slow or difficult in capturing or understanding something. So they need to be taught repeatedly until it becomes a habit to make the child understand. In addition, another similarity that causes them difficulty in learning is because they focus on things that interest them, so they cannot focus on learning. However, these obstacles do not prevent them from learning even though they often experience difficulties. Various things can be done to deal with learning difficulties in children with disabilities, especially in children with autism, ADHD and Down syndrome so that they can still get their rights and develop themselves to be better.